Strengthening the Foundations of Nationalism in the Digital Era: Threats, Challenges, and Indonesia's Strategy Towards 2045 - Rachmat Setiawibawa; Dina Subagia; Fauzia Gustarina Cempaka Timur (International Journal of Science and Society, 2026)
The development of the digital era has had a significant impact on Indonesia's social, economic, and national defense structures. Digitalization has accelerated the flow of information while simultaneously introducing a new spectrum of threats, from disinformation and cyberwarfare to ideological infiltration that have the potential to undermine the foundations of the nation. In the context of moving towards a Golden Indonesia 2045, an adaptive defense strategy is needed, particularly in the land defense dimension as the vanguard of the overall defense system. This study aims to analyze strategic threats and challenges in the digital era and formulate a relevant land defense strategy to strengthen national resilience and national identity. The method used is a descriptive qualitative approach with an analysis of strategic literature and national defense policy. The study results indicate that land defense plays a crucial role in maintaining territorial stability, strengthening nationalist values, and empowering communities as reserve and support components. The land defense strategy needs to be directed at three main aspects: (1) digital transformation in the command and control system; (2) increasing personnel capacity through digital literacy and ideological awareness; and (3) strengthening synergy between the Indonesian National Armed Forces (TNI), regional governments, and the community in maintaining land sovereignty amidst global dynamics. Thus, strengthening the foundations of nationalism in the digital era depends not only on technological advancements but also on a robust, intelligent land defense preparedness rooted in national values. This approach provides a strategic foundation for Indonesia in facing complex threats toward its ambitious vision of Golden Indonesia 2045.